STUDENTS’ MATHEMATICAL REASONING: HOW COULD IT BE THROUGH MHM-PROBLEM BASED STRATEGY AIDED INTERACTIVE MULTIMEDIA? - Runisah Runisah; wiwit Damayanti Lestari; Nurfadilah Siregar (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
AbstractThis study aims to determine students' mathematical reasoning ability using Mathematical Habits of Mind-Problem based Strategy (MHM-PB) strategy aided interactive multimedia and to analyze students' difficulties in solving mathematical reasoning ability tests. This research was carried out using the quasi-experimental method with pre-test and post-test control group design. Data were obtained from 66 grade VII students at Indramayu Regency, Indonesia using an essay test with five problems on mathematical reasoning ability. Mathematical Habits of Mind-Problem Based Strategy aided Interactive Multimedia is used in experimental class and the other class received conventional strategy. The result showed that students’ mathematical reasoning using MHM-PB strategy aided interactive multimedia was better than the conventional strategy. There is no difference in mathematical reasoning abilities based on gender in students who use MHM-PB. Furthermore, some students still have difficulty making a conclusion, providing reasons or evidence for the answers they give, and checking the truth of a statement. Meanwhile, making generalizations is a difficulty that many students experience.